ANALISIS PENGUKURAN KINERJA PEMERINTAH DAERAH DALAM ERA OTONOMI DAERAH DI KABUPATEN SORONG PROVINSI PAPUA BARAT - Ulimpa, Yohanis S.; Sondakh, Jullie J.; Runtu, Treesje (Universitas Sam Ratulangi, 2018)
In line with regional autonomy that is oriented towards empowerment (emporwerment) and community guidance in the implementation of clean authority and free of corruption, collusion and nepotism, the public sector is often regarded as a nest of wasteful efficiency and institutional fund leakage that always loses money. But the public sector still has wide opportunities to improve the performance of the benefits of resources economically, effectively and efficiently. Knowing the performance measurement of the Sorong Regency government. Knowing the role of indicators in the Sorong Regency government. The method used in this study is descriptive qualitative. The result is the performance measurement of the local government is carried out because of the provisions of the central government to make performance accountability reports for each government agency.Keywords :Performance Measurement, Performance Indicator, LAKIP, Sorong District GovernmentÂ Â Â